If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(0.3x + 2) + 3x = x + 60 Reorder the terms: 6(2 + 0.3x) + 3x = x + 60 (2 * 6 + 0.3x * 6) + 3x = x + 60 (12 + 1.8x) + 3x = x + 60 Combine like terms: 1.8x + 3x = 4.8x 12 + 4.8x = x + 60 Reorder the terms: 12 + 4.8x = 60 + x Solving 12 + 4.8x = 60 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + 4.8x + -1x = 60 + x + -1x Combine like terms: 4.8x + -1x = 3.8x 12 + 3.8x = 60 + x + -1x Combine like terms: x + -1x = 0 12 + 3.8x = 60 + 0 12 + 3.8x = 60 Add '-12' to each side of the equation. 12 + -12 + 3.8x = 60 + -12 Combine like terms: 12 + -12 = 0 0 + 3.8x = 60 + -12 3.8x = 60 + -12 Combine like terms: 60 + -12 = 48 3.8x = 48 Divide each side by '3.8'. x = 12.63157895 Simplifying x = 12.63157895
| 8t-6t=6 | | -13+-7=4 | | 6(2a+10)=-3a+25+8a | | 0.9=4.5 | | (1/9)^(-3/2) | | 10a-8a=14 | | l+15.2=-4.7 | | -2a-7= | | 3n=156 | | 20x-5=50x+19 | | (5x+2)+(3x+5)+(8x+8)+(5x+10)+(4x+15)=500 | | 3.5=4x | | log(x+15)-log(x-1)=2 | | k^2+3k=-2 | | 8n=168 | | ax+bx=b | | y=24+4x | | v/6=5/10 | | (-2x^2)+x+32=0 | | -4(2x+3)=2x+6-8x+2 | | 12n=192 | | (2x-3)(7-x)=0 | | f/7=12 | | 8+-32u= | | 0.5(x-10)=9+4x | | (1/16)^(-3/2) | | 8-(4-7)= | | 27+3x=4(-x+3)-27 | | 10+r=3r+18 | | 5(2a-4)=(2a+4) | | =c/ | | 36x(36x)=173 |